PWE-036 The Use of Amino Terminal of Type III Pro-Collagen Peptide (P3NP) to Monitor Methotrexate Associated Liver Fibrosis. (17th August 2016) - Haq, I; Sikafi, R; Aithal, GP
Abstract : Introduction: Methotrexate (MTX) is an important immunosuppressive drug commonly used to treat psoriasis and rheumatoid arthritis. Concern related to the potential of the drug to induce liver fibrosis has led to numerous guidelines on monitoring patients on methotrexate therapy. The amino terminal of type III pro-collagen peptide (P3NP) is an extension peptide that is cleaved and liberated into extracellular fluid and hence is a biomarker for collagen turnover. Increased levels occur during tissue repair and fibrosis, hence in principle P3NP has been used to monitor patients for potential adverse effect of hepatic fibrosis. Methods: We reviewed all requests for P3NP received by clinical biochemistry service at Nottingham University Hospitals between 2010 and 2015. We assessed how the results of P3NP were acted upon, what further tests and investigations were performed on patients where raised P3NP were reported. A total of 7319 assays were analysed corresponding to 495 patients. The data were analysed to see what proportion of positive results went on to have a Fibroscan, liver biopsy and to see whether histological findings correlate with P3NP level. As well as basic demographic data, we looked at co-morbidities, imaging, transient elastography and other risk factors for liver disease. Results: Of the 495 patient records examined 185 (37.3%) had a raised P3NP levels (>8 microg/L); of these, 33 (17.8%) were referred to hepatologists leading to 27/33 (69.7%) investigated with transient elastography and 8 (24.2%) having liver biopsy. Of those who had liver biopsy 6/8 (75%) showed NASH with early fibrosis and 25% showed advanced fibrosis from NAFLD; in addition to methotrexate therapy, all of these patients had one or more risk factors for NAFLD. A mean P3NP value of 11.4 correlated with NASH with any fibrosis and 16.4 microg/L correlated with advanced fibrosis. Conclusion: Despite wide spread use of P3NP, raised P3NP are not investigated adequately. Although small number of patients undergoing liver biopsy had significant histological abnormality ranging from NASH to advanced fibrosis, all had additional risk factors for NAFLD indicating that MTX treatment could therefore be stratified according to co-morbid risk factors. Disclosure of Interest: None Declared